Pedagogical competence-based Training Needs Analysis for Natural Science Teachers - Irma Febrianis; Pudji Muljono; Djoko Susanto (Journal of Education and Learning (EduLearn), 2014)
This study offers an effective approach in determining the needs of training of the teachers using the Training Needs Analysis (TNA). The objectives of the study were to obtain evidence an actual pedagogic competence of the natural sciences teachers, to obtain needs and training priorities, and proposing recommendations on the effectiveness of training method. Surveys, interviews, and FGD were conducted to get primary data. Survey was carried on 165 natural science teachers of SMP Negeri Pekanbaru using self-evaluation questionnaire. Results showed that actual pedagogic competence of the teachers was below the ideal competence. There were five priorities of training program, namely : training of ICT, classroom action research, theory and principles of learning on integrated natural science, curriculum development, and understanding of pupilsâ€™ characteristics. It is suggested that In House Training, specific training, and short courses are worth applied as effective training methods to improve pedagocical competence of the teachers.Â Â